Aluminium phosphide poisoning cases in a tertiary care hospital - Saha, Jayanto Kumar; Azad, Khan Abul Kalam; Hossain, Mohammad Zaid; Amin, Md Robed; Ahmed, Moniruzzaman; Ahsan, Hafez Md Nazmul; Rahman, Saidur (Journal of Dhaka Medical College, 2015)
Background: Aluminium phosphide is used to control rodents and pests in grain storage facilities. It produces phosphine gas, which is a mitochondrial poison. Unfortunately, there is no known antidote for aluminium phosphide intoxication and the mortality rate is very high. This type of poisoning (known as Kerry or Rice tablet poisoning) is common in Comilla region in Bangladesh. Methods: The study was an observational study and was conducted in the Department of Medicine and in Emergency Room of Comilla Medical College Hospital, Comilla, between February and August, 2013. Twenty five cases of Kerry tab. Poisoning were studied about their causes, clinical features, treatment and outcome. Results: Most of the patients (92%) were female and age range was 15-45 yrs. Familial disharmony was the main reason of their suicidal attempts. This poisoning was common in Chandina, Sadar, Debidar, Burichong, B.para, Muradnagar and Daudkandi upazillas of Comilla District. Vomiting and features of shock were the major clinical menifestations. Routine ECG was not done to these patients. Most of the patients (80%) were referred to higher centres in Dhaka after the primary management. Only 20% patients were survived due to early stomach wash and supporting medical management. One patient who survived also mentioned of taking date expired Kerry tablet. Conclusion: Strict implementation of nationwide pesticide regulation, including restricting the availability of poison, being aware of its toxicity and providing improved medical management and improved intensive care facilities can further reduce the mortality due to AlP toxicity as there is no antidote available presently. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22685 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 3-6